Peutz-Jeghers syndrome as an- emergency presentation - Sumana; Rao; Sahaja; Swaroopa; Kalyani; Venkatesh (Journal of Medical and Scientific Research, 2018)
An 18-year-old male patient presenting with mucocutaneous lesions of the face, chronic recurring abdominal pain for two years and recent swelling in the right hypochondrium for two days was investigated by CT scan. Multiple polypoidal lesions within the proximal jejunal loops were noted in addition to a large mass causing intussusception in the descending colon. Surgical decompression, imaging features and histological findings confirmed the diagnosis of Peutz-Jeghers syndrome.